SPECIFICATION OF ACCOUNTING OF FIXED ASSETS UNDER INTERNATIONAL AND RUSSIAN STANDARDS - T. Rogulenko (Publishing House of the State University of Management, 2017)
The problems of definition and recognition of fixed assets are considered. The current Accounting Regulation «Accounting for Fixed Assets» is compared with the International Standard «Fixed Assets» in terms of determining and recognizing objects in accounting and reporting.